2019
DOI: 10.1002/aoc.5416
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the first mixed ligand Mn (II) and Cd (II) complexes of 4‐methoxy‐pyridine‐2‐carboxylic acid, molecular docking studies and investigation of their anti‐tumor effects in vitro

Abstract: The first mixed ligand Mn (II) and Cd (II) complexes containing 4‐methoxy‐pyridine‐2‐carboxylic acid (4‐mpic) and 4,4′‐dimethyl‐2,2′‐bipyridine (dmbpy) were synthesized in this study. The geometric structures of [Mn(4‐mpic)2(dmbpy)] (complex 1) and [Cd(4‐mpic)2(dmbpy)] (complex 2) were determined by single crystal X‐Ray diffraction method. FT‐IR and UV–Vis spectra were also recorded to investigate vibrational and electronic properties of complexes 1 and 2. Density functional theory (DFT) calculations were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(18 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…Recent studies in the literature have revealed that some Cd(II)-based coordination complexes show interesting bioactivity. For instance, Tamer and co-workers have reported that the Cd(II)based coordination complex [Cd(4-mpic) 2 (dmbpy)] shows concentration-dependent effects in the MTT assays, which could suggest a potential use for these drug combinations in cancer cell lines [20] ; Bi and workers have prepared three metal coordination complexes based on different metal centers (Cu, Zn, and Cd), and they found that the Cd-based complex has the highest antiproliferative activity among the three complexes, which can inhibit proteasomal chymotrypsin-like activity and also can induce apoptosis on human breast cancer MDA-MB-231 cells. [21] It is generally believed that the structure and function of MOFs are determined by the organic ligand and metal ions.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…Recent studies in the literature have revealed that some Cd(II)-based coordination complexes show interesting bioactivity. For instance, Tamer and co-workers have reported that the Cd(II)based coordination complex [Cd(4-mpic) 2 (dmbpy)] shows concentration-dependent effects in the MTT assays, which could suggest a potential use for these drug combinations in cancer cell lines [20] ; Bi and workers have prepared three metal coordination complexes based on different metal centers (Cu, Zn, and Cd), and they found that the Cd-based complex has the highest antiproliferative activity among the three complexes, which can inhibit proteasomal chymotrypsin-like activity and also can induce apoptosis on human breast cancer MDA-MB-231 cells. [21] It is generally believed that the structure and function of MOFs are determined by the organic ligand and metal ions.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…[18][19][20] It was reported that some metal ion chelators that have shown promising antitumor activity include heterocyclic carboxaldehyde thiosemicarbazones, analogs of pyridoxal isonicotinoyl hydrazone, and other natural and synthetic chelators. 21,22 Due to the effective complexation ability of the pyridine ring and carboxylic acid group, pyridine-2-carboxylic acid and its derivates have attracted extensive attention as a potential chelating ligand. [22][23][24][25] In our previous study, Mn (II) and Cd (II) complexes of 4-methoxy-pyridine-2-carboxylic acid were synthesized and tested on human breast carcinoma cell line MCF-7.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Due to the effective complexation ability of the pyridine ring and carboxylic acid group, pyridine-2-carboxylic acid and its derivates have attracted extensive attention as a potential chelating ligand. [22][23][24][25] In our previous study, Mn (II) and Cd (II) complexes of 4-methoxy-pyridine-2-carboxylic acid were synthesized and tested on human breast carcinoma cell line MCF-7. 22 The obtained results demonstrated that the final complexes exhibit a higher inhibitory effect than both metal salts and ligands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the produced complexes spectra, these bands alter in shape and shift to lower wavenumbers (1682-1605) cm −1 indicated metal coordination with nitrogen in the benzothiazole ring (Sagdinc et al 2009). As can be seen in the spectrum of free ligand, strong band at 1497 cm −1 attributed to υ(N=N) stretching, because of the complexity associated with metal ions, this band is changing to a lower frequency and reduced in intensity (Tamer et al 2020). In addition, the spectrum shows the band at 1266 cm −1 , which correspond to the υ(C-S) of the benzothiazole ring.…”
Section: Mass Spectral Analysismentioning
confidence: 95%